The Swedish marine nematologist Carl Allgén (1886–1960): a bio-bibliography and his collection - Boström, Sven; Holovachov, Oleksandr (Zootaxa, 2017)
The Swedish marine nematologist Carl Allgén (1886–1960) published 185 scientific papers on parasitic, terrestrial, limnic and especially marine nematodes between 1921 and 1960. Among them are also some papers on species of suctorians found mostly on desmodorid nematodes. He described about 70 new genera and over 800 new species and subspecies of nematodes. Allgén left a large collection of nematodes to the Swedish Museum of Natural History in Stockholm and it is now deposited in the invertebrate collection of the Zoology department. The collection comprises about 4500 slides in total, with about 310 slides containing type specimens collected from the Arctic to Antarctica. Allgén’s publications have to a large extent been ignored by scientists working on marine nematodes, likely because of the poor quality of many of his species descriptions. The authors want to remind the scientific community about the existence of Allgén’s collection, its availability for study and its importance for nematode taxonomy and systematics. A complete list of Allgén’s publications, a list of all species described by him, and a list of type material available is presented.